(untitled) - CORPORATION MICROSOFT (USA, 1991)
1.The programmers workbench / 2.Quick start / 3.Managing multimodule programs / 4.User interface details / 5.Advanced PWB techniques / 6.Customizing PWB / 7.Programmers workbench reference / 8.Getting Started with codeview / 9.The codeview environment / 10.Special topics / 11.Using expressions in codeview / 12.Codeview reference / 14.CL Command reference / 15.Linking object files with LINK / 16.Creating overlaid DOS programs / 17.Creating module-Definition files / 18.Using EXEHDR / 19.Managing projects with NMAKE / 20.Managing libraries with LIB / 21.Creating help files with HELPMAKE / 22.Browser utilities / 23.Using other utilities / 24.Using help
Incluye indice pag.819 / Glosario pag.803 / Apendice pag.777
Keywords: LENGUAJES DE PROGRAMACION